Legal Aspects of Innovations in Croatia – Practical Guide and Highlights - Dijana Zoričić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
Innovation is the key term of development in the modern world. Although it is of the utmost importance, there is still a lot to be done to popularize the idea of innovation, to ensure a common approach to the necessity of providing incentives, and of tightening the relevant legislation ensuring the protection of innovations and innovators. In the last decades, the legislation on innovations in Croatia has changed and improved remarkably. As a direct result of great social and legal efforts, the innovative environment flourishes, influencing directly the economic and social growth of the country. Through a review of the Croatian legislation, this paper shows the dynamics of the development of legislation in the field of innovations. The very term “innovation” has been reassessed as there was a very common misunderstanding of the difference between invention and innovation. Croatian innovators are more and more successful at global level and this has been confirmed by recent awards.
Keywords: K11; 330; innovations; legislation; intellectual property rights; Croatia